Entrepreneurship, Entrepreneurial Values, and Public Policy in Argentina - Jose Anchorena; Lucas Ronconi (Inter-American Development Bank (IDB), 2012)
This paper uses datasets from six surveys to describe entrepreneurship in Argentina. While the quantity of entrepreneurship in Argentina is high, its quality is low, given the high proportion of informal and necessity entrepreneurs. Income is found to play a greater role in determining probability of becoming an entrepreneur than parental wealth; entrepreneurship is, however, transmitted inter- generationally. Although it is found that Argentina promotes entrepreneurial values more than most Latin American countries, entrepreneurs face several obstacles. Finally, using panel data based on household surveys, the paper estimates the short and long-run effects of an increase in public employment on entrepreneurship, finding the effects to be negative and strong. Overall, the evidence suggests that changes in public policies and other areas are needed for Argentina to become an entrepreneurial economy.
Keywords: L26; L5; O17; 330